2014
DOI: 10.3390/ijms150814058
|View full text |Cite
|
Sign up to set email alerts
|

Association between Phosphatase Related Gene Variants and Coronary Artery Disease: Case-Control Study and Meta-Analysis

Abstract: Recent studies showed that the serum alkaline phosphatase is an independent predictor of the coronary artery disease (CAD). In this work, we aimed to summarize the association between three phosphatase related single nucleotide polymorphisms (rs12526453, rs11066301 and rs3828329) and the risk of CAD in Han Chinese. Our results showed that the rs3828329 of the ACP1 gene was closely related to the risk of CAD in Han Chinese (OR = 1.45, p = 0.0006). This significant association of rs3828329 with CAD was only foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…These observations are in line with the results discussed by Han Xia et al 2014, where the phosphatase-related single nucleotide polymorphism, rs12526453 was significantly associated with coronary artery disease (CAD) risk in multiple populations. [23] rs10757274 and rs10757278 were seen to increase the levels of the risk marker, PLAC ( P < .05), thus, these polymorphisms can be considered as major risk factors contributing to the risk of developing CVDs as described earlier. [24,25] Nevertheless, the comparative analysis also revealed that the SNPs, rs1801133, rs1549758, rs1799983, rs5082, and rs5186 were found to be significantly associated with cardioprotective markers such as HDL and ApoA1.…”
Section: Discussionmentioning
confidence: 82%
“…These observations are in line with the results discussed by Han Xia et al 2014, where the phosphatase-related single nucleotide polymorphism, rs12526453 was significantly associated with coronary artery disease (CAD) risk in multiple populations. [23] rs10757274 and rs10757278 were seen to increase the levels of the risk marker, PLAC ( P < .05), thus, these polymorphisms can be considered as major risk factors contributing to the risk of developing CVDs as described earlier. [24,25] Nevertheless, the comparative analysis also revealed that the SNPs, rs1801133, rs1549758, rs1799983, rs5082, and rs5186 were found to be significantly associated with cardioprotective markers such as HDL and ApoA1.…”
Section: Discussionmentioning
confidence: 82%
“…COL5A2 was also reported as a novel candidate marker for the identification and treatment of ischemic cardiovascular disease ( 34 ). PTPN11 was reported to contain a CAD risk variant ( 35 ). SMAD3 was reported to be associated with CAD and suggested to be a useful biomarker for diagnosis and risk stratification ( 36 ).…”
Section: Evaluation Of Gwab Using Disease Gwas Datamentioning
confidence: 99%
“…I have read with interest the recent paper by Han and coworkers [ 1 ] on the putative effects of a PHACTR1 variant in the context of coronary artery disease. The authors conclude to a significant risk-enhancing role of rs12526453 on the grounds of 19 earlier case-control studies.…”
mentioning
confidence: 99%
“…Thus, cases and controls have been muddled [ 2 ], fictitious cases and controls have been introduced (e.g., from a genome-wide association study phase that did not include rs12526453 [ 3 ]), odds ratios have been altered [ 4 , 5 ] and quantitative traits have been arbitrarily dichotomized post hoc to fit in a case-control design [ 6 ]. Other inconsistencies include discrepant measures of effect size (e.g., Table 5 and Figure 3 [ 1 ]), contradictory numbers in article retrieval (see Figure 1 [ 1 ]), missing data points (see Figure 5 [ 1 ]) and utterly erratic referencing.…”
mentioning
confidence: 99%